INVESTIGATIONS OF RESISTANCE TO SEIZING OF LASER-TEXTURED ELEMENTS - Antoszewski, Bogdan (Bulletin of Sumy National Agrarian University. The series: Mechanization and Automation of Production Processes)
The paper presents results of experiments concerning the assessment of the texture effect on scuffing resistance. The results showed that texturing causes an increase in scuffing resistance. In addition, textures showing lower surface energy and having higher volume were found to form surfaces more resistant to scuffing.